2021
DOI: 10.1001/jamainternmed.2021.3108
|View full text |Cite
|
Sign up to set email alerts
|

Association Between a Common, Benign Genotype and Unnecessary Bone Marrow Biopsies Among African American Patients

Abstract: he observation of lower mean white blood cell (WBC) counts among individuals of African ancestry compared with those of European ancestry is well established. [1][2][3][4] The clinical finding of low WBC counts among healthy individuals of African ancestry is variably designated benign ethnic neutropenia and is not associated with an increased risk of infection. [5][6][7] This phenomenon is attributed, in large part, to homozygosity for the rs2814778-C variant in the promoter of ACKR1 (OMIM 613665) gene. Loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 20 publications
(22 reference statements)
0
26
0
Order By: Relevance
“…These data suggest that Black individuals are more susceptible to an unnecessary, invasive, and painful procedure than White individuals due to frequent carriage of a benign genotype. Furthermore, the cost of a bone marrow biopsy at our medical centre is approximately $6000, significantly less than Duffy antigen testing, which costs less than $200 when performed in most laboratories and blood banks 12 . Omission of an unnecessary BMB would decrease health care utilization costs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These data suggest that Black individuals are more susceptible to an unnecessary, invasive, and painful procedure than White individuals due to frequent carriage of a benign genotype. Furthermore, the cost of a bone marrow biopsy at our medical centre is approximately $6000, significantly less than Duffy antigen testing, which costs less than $200 when performed in most laboratories and blood banks 12 . Omission of an unnecessary BMB would decrease health care utilization costs.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing whether an individual carried the Duffy Null phenotype would indicate whether a lower ANC value may reflect a benign predisposition. In support of a role for genotyping/phenotyping, a retrospective study of individuals of Black race treated at three medical centres who had a BMB to investigate an isolated low white blood cell count, 97% of individuals carried the rs2814778‐CC (Duffy Null) genotype 12 . Furthermore, 97% of the biopsies among genotype carriers demonstrated benign findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Benign Ethnic Neutropenia (BEN) is observed predominantly in African Americans, but specifically is strongly associated with the variant at rs2814778 [65], [66]. Recent studies have suggested that genotype screening at rs2814778 could aid in the interpretation of neutropenia in African Americans and avoid unnecessary invasive procedures as well as lead to an increase of the inclusion of these individuals to various treatments [67]. Additionally, the Kidney Donor Risk Index (KDRI) equation uses race as a risk factor [68], but it has been recently proposed to use the presence of APOL1 variants as a factor instead [69].…”
Section: Discussionmentioning
confidence: 99%